Translation and validation of the Schizophrenia Caregiver Questionnaire – Japanese version (J-SCQ) - Naotoshi Kamizawa; Toshihiro Miyamura (Heliyon, 2023)
The Schizophrenia Caregiver Questionnaire (SCQ) was developed to evaluate the state of family members caring for schizophrenics. Our study aimed to construct a Japanese version of the SCQ (J-SCQ) based on its English version and verify its reliability and validity. We conducted forward and backwards translations and cognitive debriefing to draw up the J-SCQ. A total of 1229 survey sheets were mailed, together with the Japanese versions of the Medical Outcomes Study Short-Form version 2 (SF-12v2) and World Health Organization Quality of Life Scale (WHOQOL-26) questionnaires. A total of 305 survey sheets (valid response rate: 68.2%) were analyzed. The Cronbach’s alpha coefficients of various supra-domains and subdomains of the J-SCQ were over 0.71, establishing its internal consistency. Pearson’s correlation coefficients between the various domains of the SF-12v2 and WHOQOL-26 was used to establish concurrent validity. The results show that the J-SCQ may be a useful Japanese questionnaire that can compare Japanese caregivers to those across different countries and measure the effects of support and intervention provided to caregivers.